The Arctic Five: search for a balance of power in the region - I. S. Doroshenko (Проблемы постсоветского пространства, 2020)
Due to climate change, the Arctic region becomes a place of geopolitical rivalry of both Arctic and non-Arctic states. Traditional formats for determining the agenda in the region are effective, but with the advent of the interest of an increasing number of international actors, these formats are transforming, which may affect the balance of power in the region. The growing activity of Asian countries in the Arctic, primarily China, is forcing regional states to make adjustments to the development strategy of the region. The rapid renewal of its potential in the northern territories of Russia caused a negative reaction from the western countries, especially after 2014.Such aspirations have emerged as the internationalization of the region by Northern Europe and China, the desire to draw clear boundaries on the part of Russia and Canada, and the buildup of US influence on its colleagues in the North Atlantic bloc. This situation may cause an uncontrolled increase in tension in the region, especially if new alliances between the Arctic and non-Arctic countries are created. The author considers the current approaches of the countries of the Arctic five, analyzes the true motives of internationalization and the role of the format of the Arctic five in maintaining a balance of power and stability in the northern latitudes.